A discrete mechanics approach for musculoskeletal simulations with muscle wrapping - Penner, Johann; Leyendecker, Sigrid (Multibody System Dynamics, 2022)
In this work, we apply discrete variational calculus to the muscle wrapping problem to simulate musculoskeletal systems. This is the prediction of the action of muscles working around joints, in conjunction with skeletal movements that are represented as a multibody system. Thereby, we transfer principles of the calculus of variations to their discrete counterparts in order to solve the shortest path problem. A key advantage of this formulation is that the structure preserving properties of the integrator enable the simulation to account for large, rapid changes in muscle paths at relativity moderate computational costs. In particular, the derived muscle wrapping formulation does not rely on special case solutions, has no nested loops, has a modular structure and is completely described by algebraic time-stepping equations.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Discrete mechanics; Discrete variational principle; Muscle wrapping; Musculoskeletal multibody simulations